A moderate oestradiol level enhances neutrophil number and activity in muscle after traumatic injury but strength recovery is accelerated. (24th August 2018) - Le, Gengyun; Novotny, Susan A.; Mader, Tara L.; Greising, Sarah M.; Chan, Sunny S. K.; Kyba, Michael; Lowe, Dawn A.; Warren, Gordon L.
Abstract : Key points: The female hormone oestrogen may protect muscle from injury by reducing inflammation but this is debatable. In this study, the inflammatory response of injured muscle from oestrogen‐replete mice was comprehensively compared to that from oestrogen‐deficient mice. We show that oestrogen markedly promotes movement of neutrophils, an inflammatory white blood cell type, into muscle over the first few days after injury but has only a minor effect on the movement of macrophages, another inflammatory cell type. Despite the enhancement of inflammation by oestrogen in injured muscle, we found strength in oestrogen‐replete mice to recover faster and to a greater extent than it does in oestrogen‐deficient mice. Our study and others indicate that lower doses of oestrogen, such as that used in our study, may affect muscle inflammation and injury differently from higher doses. Abstract: Oestrogen has been shown to protect against skeletal muscle injury and a reduced inflammatory response has been suggested as a possible protective mechanism. There are, however, dissenting reports. Our objective was to conduct an unbiased, comprehensive study of the effect of oestradiol on the inflammatory response following muscle injury. Female C57BL6/J mice were ovariectomized and supplemented with and without oestradiol. Tibialis anterior muscles were freeze injured and studied primarily at 1–4 days post‐injury. Oestradiol supplementation increased injured muscle gene expression of neutrophil chemoattractants ( Cxcl1 and Cxcl5 ) and to a lesser extent that of monocyte/macrophage chemoattractants ( Ccl2 and Spp1 ). Oestradiol markedly increased gene expression of the neutrophil cell surface marker ( Ly6g ) but had less consistent effects on the monocyte/macrophage cell surface markers ( Cd68, Cd163 and Cd206 ). These results were confirmed at the protein level by immunoblot with oestradiol increasing LY6G/C content and having no significant effect on CD163 content. These findings were confirmed with fluorescence‐activated cell sorting counts of neutrophils and macrophages in injured muscles; oestradiol increased the proportion of CD45 + cells that were neutrophils (LY6G + ) but not the proportion that were macrophages (CD68 + or CD206 + ). Physiological impact of the oestradiol‐enhanced neutrophil response was assessed by strength measurements. There was no significant difference in strength between oestradiol‐supplemented and ‐unsupplemented mice until 2 weeks post‐injury; strength was 13–24% greater in supplemented mice at 2–6 weeks post‐injury. In conclusion, a moderate level of oestradiol supplementation enhances neutrophil infiltration in injured muscle and this is associated with a beneficial effect on strength recovery. Key points: The female hormone oestrogen may protect muscle from injury by reducing inflammation but this is debatable. In this study, the inflammatory response of injured muscle from oestrogen‐replete mice was comprehensively compared to that from oestrogen‐deficient mice. We show that oestrogen markedly promotes movement of neutrophils, an inflammatory white blood cell type, into muscle over the first few days after injury but has only a minor effect on the movement of macrophages, another inflammatory cell type. Despite the enhancement of inflammation by oestrogen in injured muscle, we found strength in oestrogen‐replete mice to recover faster and to a greater extent than it does in oestrogen‐deficient mice. Our study and others indicate that lower doses of oestrogen, such as that used in our study, may affect muscle inflammation and injury differently from higher doses.